2014
DOI: 10.1007/s00240-014-0742-4
|View full text |Cite
|
Sign up to set email alerts
|

Does aging affect the outcome of percutaneous nephrolithotomy?

Abstract: To investigate whether aging affects surgical outcomes by comparing the results of two patient groups undergoing PNL: those over 60 and those under 60. A retrospective screen was made for patients undergoing conventional PNL surgery for renal stones performed in two separate centers between 2010 and 2013. 520 patients included were classified into age groups: patients aged 18-59 comprised Group-1 and those aged over 60 comprised Group-2. Those between 60-69 years (sexagenarian) were assigned to Group-2a; 70-79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
2
5
1
Order By: Relevance
“…Diabetes mellitus was the comorbidity that exhibited a significant difference between the older and younger age groups, with 30.8% of the older patients having diabetes mellitus compared to 18.9% of the younger patients (p=0.071). Similar findings were discovered in two prior studies by Abedali et al (2019) and Buldu et al (2015), in which diabetes mellitus was shown to be considerably more prevalent in the older age group investigated. In a study conducted by Wei et al (2015), diabetes was found to be significantly associated with an increased frequency of postoperative and infectious complications following PCNL.…”
Section: Discussionsupporting
confidence: 91%
“…Diabetes mellitus was the comorbidity that exhibited a significant difference between the older and younger age groups, with 30.8% of the older patients having diabetes mellitus compared to 18.9% of the younger patients (p=0.071). Similar findings were discovered in two prior studies by Abedali et al (2019) and Buldu et al (2015), in which diabetes mellitus was shown to be considerably more prevalent in the older age group investigated. In a study conducted by Wei et al (2015), diabetes was found to be significantly associated with an increased frequency of postoperative and infectious complications following PCNL.…”
Section: Discussionsupporting
confidence: 91%
“…Kuzgunbay et al (15) evaluated the results of 300 PNL procedures, and Nakamon et al (16) examined 446 patients who had undergone PNL; there were no statistically significant differences in the length of hospital stay when both elderly and younger patients were compared in these two series. However, other reports have found that elderly patients had a longer hospital stay compared with younger patients (11). Our results indicated that the average length of stay was three days in Group 1 and four days in Group 2, which was not statistically significant (p: 0.164).…”
Section: Discussioncontrasting
confidence: 80%
“…Buldu et al (11) investigated whether aging impacted surgical outcomes in PNL and did not find a statistically significant difference in the mean duration of surgery, postoperative hematocrit drop, or the complication and success rates between younger and elderly groups. Similarly, in our study, the stone-free, clinically insignificant residual fragment , and clinically significant residual fragment rates were 66.2%, 8.2%, and 25.6%, respectively, in Group 1 and 71.9%, 3.1%, and 25%, respectively, in Group 2; no significant difference was observed (p: 0.569).…”
Section: Discussionmentioning
confidence: 99%
“…Anagnostou et al showed that they achieved stone-free 73.3% in the geriatric group with a stone burden of 56.7 mm 3 , indistinguishable from the youth (15). Over the years, stone-free rates in the elderly have also increased and reached 90% in the literature (16). In this case, the experience of the surgeon is also an important factor (17).…”
Section: Discussionmentioning
confidence: 98%